IMPLEMENTASI MODUL PEMANTAUAN PERTUMBUHAN BALITA BAGI KADER POSYANDU DAN IBU BALITA (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Stunting is currently a nutritional problem caused by multifactors and requires multisectoral treatment. The potential of posyandu cadres as drivers of the health sector, especially monitoring the growth of toddlers to increase knowledge and skills in helping prevent and overcome nutritional problems (stunting). The problem of stunting in the partner village (Tawangsari village) shows that the provision of food (ASI and MP-ASI) for infants and under-fives is not optimal. The goal of this activity is to increase the knowledge of health cadres and mothers of stunting toddlers about the importance of providing complementary feeding and the practice of food processing techniques made from local foods as the basic ingredients in making MP-ASI and growth monitoring of toddlers. This training is lecture, discussion, demonstration and simulation. Activity is that there is an increase in nutritional knowledge of posyandu cadres and mothers of children under five growth monitoring.